Konsep Desain Health Resort and Spa dengan Identitas Arsitektur Nusantara Kontemporer di Desa Keboireng - Milda Uswatul Kamila; Diyah Ayu Saputri (Konstruksi: Publikasi Ilmu Teknik, Perencanaan Tata Ruang dan Teknik Sipil, 2026)
The village of Keboireng is located in Besuki District. Keboireng Village offers both natural and man-made tourism potential. The natural tourist attractions in Keboireng Village include Klatak Beach, Gemah Beach, Bayem Beach, and the Rice Field Tour. To capitalize on this natural potential, a health resort and spa has been designed specifically for local tourists seeking a peaceful atmosphere far from the city after being exhausted from various activities, thus requiring a tourist destination capable of providing a calm and peaceful ambiance along with facilities for physical relaxation. The Contemporary Nusantara Architecture concept was chosen with the aim of introducing local culture through the design. The methods employed include literature reviews, resort standards, and spatial standards. The result of this design is a resort featuring primary facilities such as accommodations and a spa, along with the addition of a water park as a water sport attraction within the health resort and spa design, while prioritizing the use of local materials and incorporating distinctive elements of the Tulungagung region.